2011
DOI: 10.1590/s1806-37132011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho funcional de pacientes com fibrose cística e indivíduos saudáveis no teste de caminhada de seis minutos

Abstract: Objective: To compare patients with cystic fibrosis and healthy individuals in terms of their functional performance on the six-minute walk test (6MWT). Methods: A prospective, cross-sectional study involving healthy individuals and patients with cystic fibrosis treated at a referral university hospital in the city of Campinas, Brazil. The 6MWT was administered in accordance with the American Thoracic Society guidelines, and it was repeated after a 30-min rest period. For all of the participants, RR, HR, SpO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
3
17
0
7
Order By: Relevance
“…In contrast, we found no association between TRV and the 6 MWT distance. The limited distances achieved by our patients during the 6 MWT were comparable to those recently reported in children with SCD [40], [41], and in children with different chronic conditions such as juvenile idiopathic arthritis, hemophilia, spina bifida, and mildly to moderately symptomatic cystic fibrosis [42], [43]. Interestingly, Waltz et al showed that a high level of anemia, low fetal hemoglobin expression, and low red blood cell deformability independently predicted poor 6 MWT performance [41].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, we found no association between TRV and the 6 MWT distance. The limited distances achieved by our patients during the 6 MWT were comparable to those recently reported in children with SCD [40], [41], and in children with different chronic conditions such as juvenile idiopathic arthritis, hemophilia, spina bifida, and mildly to moderately symptomatic cystic fibrosis [42], [43]. Interestingly, Waltz et al showed that a high level of anemia, low fetal hemoglobin expression, and low red blood cell deformability independently predicted poor 6 MWT performance [41].…”
Section: Discussionsupporting
confidence: 85%
“…However, there was no significant correlation between the 6MWT and the gender. Similarly, Pereira et al, 15 who compared functional performance during the 6MWT of 55 patients with cystic fibrosis with 115 healthy individuals, with a mean age of 12.2 ± 4.3 years and 11.3 ± 4.3 years respectively, found that sex has no influence on walk distance of the 6MWT, whose correlations occur only with age, weight and height.…”
Section: Discusionmentioning
confidence: 90%
“…21 At the end of the test and three minutes later, the values of the HR, FR, SpO 2 , PA and modified Borg scale variables were measured, the evaluator again checked the same variables. 15 The mean distance of the 6MWT is 576m for men and 494m for women. 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of exercise in patients with CF include improved aerobic conditioning, decreased progression of lung disease, and enhanced bronchial hygiene through an increased ciliary beat frequency, activation of immune cells, reduced susceptibility to viral infections, and increased anti-inflammatory activity. Thus, patients experience a better quality of life [ 1 , 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%